Oviposition Deterrence and Immature Survival of Filth Flies (Diptera: Muscidae) When Exposed to Commercial Fungal Products. Issue 1 (14th June 2016) - Machtinger, E.T.; Weeks, E.N.I.; Geden, C. J.
Abstract: Filth flies are pests of livestock, and can transmit pathogens that cause disease to animals and their caretakers. Studies have shown successful infection of adult filth flies following exposure to different strains and formulations of entomopathogenic fungi. This study aimed to examine the effects of commercial formulations of Beauveria bassiana (Balsamo) (Moniliales: Moniliaceae) (i.e., BotaniGard ES, Mycotrol O, balEnce), and Metarhizium brunneum (Metsch.) (Ascomycota: Hypocreales) (i.e., Met52 EC), on filth fly oviposition and immature fly survival after exposure. House flies, Musca domestica L., laid significantly fewer eggs on Met52 EC-treated surfaces than on surfaces treated with all other products and the control. Similar numbers of eggs were laid on surfaces treated with all B. bassiana products, but egg production was half of the control. Stable flies, Stomoxys calcitrans (L.), laid the fewest eggs on Met52 EC- and Mycotrol O-treated surfaces. This species did not distinguish between the remaining products and the control. In a second experiment, house fly eggs were placed on treated cloths so that hatched larvae contacted the treatment prior to development. Met52 EC had the greatest effect on immature survival with a significant reduction in recovered pupae at the medium and high doses of fungi. Overall, Met52 EC, containing M. brunneum, had the greatest effect on house fly and stable fly oviposition deterrence and immature development of house flies. Management implications are discussed.